2021
DOI: 10.1002/mds.28566
|View full text |Cite
|
Sign up to set email alerts
|

High‐Frequency Oscillations in the Pallidum: A Pathophysiological Biomarker in Parkinson's Disease?

Abstract: A BS TRACT: Background: Abnormal oscillatory neural activity in the beta-frequency band (13-35 Hz) is thought to play a role in Parkinson's disease (PD); however, increasing evidence points to alterations in high-frequency ranges (>100 Hz) also having pathophysiological relevance. Objectives: Studies have found that power in subthalamic nucleus (STN) high-frequency oscillations is increased with dopaminergic medication and during voluntary movements, implicating these brain rhythms in normal basal ganglia func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…We tested eiDBS in-vivo with the study participant using the stimulation parameters found to be optimal (stimulation at 2 mA and phase angles equal to -85 and 95 deg for suppression and amplification). eiDBS was capable of suppressing or amplifying pallidal activity in the targeted frequency interval (16)(17)(18)(19)(20)(21)(22). See Figs.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We tested eiDBS in-vivo with the study participant using the stimulation parameters found to be optimal (stimulation at 2 mA and phase angles equal to -85 and 95 deg for suppression and amplification). eiDBS was capable of suppressing or amplifying pallidal activity in the targeted frequency interval (16)(17)(18)(19)(20)(21)(22). See Figs.…”
Section: Resultsmentioning
confidence: 98%
“…Using the patient-specific ER mathematical models and recorded LFP data, we constructed a computer simulation (Fig. 2A,B) to characterize the neural modulation attained with eiDBS and search for the stimulation parameters (amplitude and phase angle) that maximized suppression and amplification of neural activity in the targeted band (16)(17)(18)(19)(20)(21)(22). See optimization curve in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations